2018
DOI: 10.19195/1899-5101.11.2(21).5
|View full text |Cite
|
Sign up to set email alerts
|

Propaganda against the West in the Heart of Europe. A masked offi cial state campaign in Hungary

Abstract: There is a twofold crisis in Europe: While mass migration is a serious challenge to the whole EU, we also have member-states striking at the EU itself. Our research shows that Hungary, with its overwhelming political communication, became the first post-socialist EU member state to run official anti-Western propaganda since the end of the Cold War and it seems that other CEEcountries will follow its lead. The campaign does not go against Brussels directly: the real message is hidden between the lines. We analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…Landscape before the Referendum Hungary's state-level administrative inexperience, its population's lack of reallife experience with migrants, and its governments' nativist populism came up against a strong state campaign against migrants through various national media. Previous research has already shown that this campaign was propagandistic in its essence, with a political agenda against the eU itself, 13 increasing xenophobia and decreasing support for immigration in Hungary. 14 at the time of the referendum, migrants were securitized as an existential threat to the Hungarian nation, with the active contribution of government and pro-government media.…”
Section: Media Representation Of Immigrants and The Hungarian Mediamentioning
confidence: 99%
“…Landscape before the Referendum Hungary's state-level administrative inexperience, its population's lack of reallife experience with migrants, and its governments' nativist populism came up against a strong state campaign against migrants through various national media. Previous research has already shown that this campaign was propagandistic in its essence, with a political agenda against the eU itself, 13 increasing xenophobia and decreasing support for immigration in Hungary. 14 at the time of the referendum, migrants were securitized as an existential threat to the Hungarian nation, with the active contribution of government and pro-government media.…”
Section: Media Representation Of Immigrants and The Hungarian Mediamentioning
confidence: 99%
“…A content analysis of a governmental site (kormany.hu) and two pro-government news sites (888.hu, magyaridok.hu) looking into a total of 1248 articles in September 2016 found 644 articles that were linked to migration, which amounts to 51%, as opposed to between 17% and 40% in critical outlets (such as index.hu and 444.hu). Most of these articles (53%) used a war terminology, suggesting that Hungarian culture must be defended from both migrants and ‘Brussels bureaucrats’ who wanted to ‘impose’ a resettlement quota on Hungary (Demeter, 2018). An automated content analysis of over 10,000 photographs published between September 2014 and June 2016 on online news outlets found that these typically portrayed migrants as a faceless flood and as criminals, not as a heterogeneous group of individuals (Fülöp et al, 2017).…”
Section: The Campaign Messagesmentioning
confidence: 99%
“…The messages delivered were labelled as ‘government information’, but many analysts described them as ‘propaganda campaigns’ (Bátorfy, 2017; Demeter, 2018; Máriás et al, 2017). This latter interpretation seems warranted in that the campaigns were not aimed at promoting a meaningful and well-informed rational-critical discussion on migration, but met several criteria of political propaganda: they included both recurring and new elements in order not to become too repetitive; they communicated simple messages meeting existing stereotypes; they promoted conspiracy theories; they offered a black-and-white interpretation of real-life events; they appealed to basic instincts such as fear; and—perhaps most importantly—they portrayed migrants as potential terrorists, that is aggressors, not victims (on propaganda, see Brown, 1971 [1963]; Klemperer, 1984 [1947]; Lasswell, 1927).…”
Section: Final Remarks: the Campaigns And Their Impactmentioning
confidence: 99%
“…On the one hand, anti-Brussels populist rhetoric emerged in the government's and the prime minister's political agenda. On the other hand, an anti-migrant campaign was still overwhelming in 2015 and in 2016 in the government's communication (Bernáth & Messing, 2015;Demeter, 2018). This rhetoric contained simultaneously vertical and horizontal elements of populist (political) communication: The antagonist, dilettante elite pushed Europe in the wrong direction, which could mean the end of the Christian Europe, while migrants did not want to assimilate to European culture, and finally the continent could not be protected from the expansion of foreign migrant groups.…”
Section: Introductionmentioning
confidence: 99%
“…After 2010 Fidesz-KDNP won three elections in a row, therefore it became the most influential party in Hungary. Scholars consider Fidesz-KDNP and its leader, the prime minister, Viktor Orbán as populists because of the anti-elitist (critique against Brussels, George Soros and rival Hungarian parties) and exclusionist (opposition towards migrants) rhetoric they used from 2015 (Bernáth & Messing, 2015;Demeter, 2018). Nonetheless, "only few articles refer to the post-2010 Fidesz government" (Csigó & Merkovity, 2016, p. 299).…”
Section: Introductionmentioning
confidence: 99%